Reproducibility of myocardial T 1 and T 2 relaxation time measurement using slice‐interleaved T 1 and T 2 mapping sequences - Bellm, Steven; Basha, Tamer A.; Shah, Ravi V.; Murthy, Venkatesh L.; Liew, Charlene; Tang, Maxine; Ngo, Long H.; Manning, Warren J.; Nezafat, Reza (Journal of magnetic resonance imaging, 2016)
To assess measurement reproducibility and image quality of myocardial T and T maps using free-breathing slice-interleaved T and T mapping sequences at 1.5 Tesla (T). Eleven healthy subjects (33 ± 16 years; 6 males) underwent a slice-interleaved T and T mapping test/retest cardiac MR study at 1.5T on 2 days. For each day, subjects were imaged in two sessions with removal out of the magnet and repositioning before the subsequent session. We studied measurement reproducibility as well as the required sample size for sufficient statistical power to detect a predefined change in T and T . In a separate prospective study, we assessed T and T map image quality in 241 patients (54 ± 15 years; 73 women) with known/suspected cardiovascular disease referred for clinical cardiac MR. A subjective quality score was used to assess a segment-based image quality. In the healthy cohort, the slice-interleaved T measurements were highly reproducible, with global coefficients of variation (CVs) of 2.4% between subjects, 2.1% between days, and 1.7% between sessions. Slice-interleaved T mapping sequences provided similar reproducibility with global CVs of 7.2% between subjects, 6.3% between days, and 5.0 between sessions. A lower variability resulted in a reduction of the required number of subjects to achieve a certain statistical power when compared with other T mapping sequences. In the subjective image quality assessment, >80% of myocardial segments had interpretable data. Slice-interleaved T and T mapping sequences yield highly reproducible T and T measurements with >80% of interpretable myocardial segments. J. Magn. Reson. Imaging 2016;44:1159-1167.